Magnetism: Another Idiosyncrasy of Boron?. Issue 13 (11th March 2021) - Vignolo, Maurizio; Bovone, Gianmarco; Capra, Marco; Loria, Federico; Bernini, Cristina; Vileno, Bertrand; Mager, Loïc; Donnio, Bertrand; Rastei, Mircea V.; Gallani, Jean‐Louis
Abstract: We have studied the magnetic properties of various Boron particles obtained by different methods and have found evidence of soft ferromagnetism in all. While our study cannot unequivocally exclude that Boron is at the origin of the magnetism, we suggest that various impurities which are either the result of the synthetic process or come from the intentional doping of the Boron particles are indeed responsible for the observed magnetic properties. The phenomenon bears similarities with what is observed in magnetic oxides such as MgO or ZnO. Abstract : Magnetometry measurements on Boron particles reveal that they exhibit soft ferromagnetism at room temperature. The magnetic properties are provisonally ascribed to structure defects or embedded impurities such as oxygen and carbon.